2000
DOI: 10.1029/1999wr900296
|View full text |Cite
|
Sign up to set email alerts
|

Determination of hydrologic pathways during snowmelt for alpine/subalpine basins, Rocky Mountain National Park, Colorado

Abstract: Abstract. Alpine/subalpine ecosystems in Rocky Mountain National Park may be sensitive to atmospherically derived acidic deposition. Two-and three-component hydrograph separation analyses and correlation analyses were performed for six basins to provide insight into streamflow generation during snowmelt and to assess basin sensitivity to acidic deposition. Three-component hydrograph separation results for five basins showed that streamflow contained from 42 to 57% direct snowmelt runoff, 37 to 54% subsurface w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
97
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 40 publications
9
97
0
Order By: Relevance
“…The snowmelt contribution increased as the freshet period progressed and peaked with high contributions at the beginning of June. Beaulieu et al (2012) and Sueker et al (2000) reported comparable results for their physically similar catchments during peak melt with 62 and up to 76 % event water contributions to streamflow, respectively. At the event-scale comparable studies are rare.…”
Section: Hydrograph Separation Results and Inferred Runoff Generationsupporting
confidence: 61%
“…The snowmelt contribution increased as the freshet period progressed and peaked with high contributions at the beginning of June. Beaulieu et al (2012) and Sueker et al (2000) reported comparable results for their physically similar catchments during peak melt with 62 and up to 76 % event water contributions to streamflow, respectively. At the event-scale comparable studies are rare.…”
Section: Hydrograph Separation Results and Inferred Runoff Generationsupporting
confidence: 61%
“…This mechanism is referred to as "fill and spill" in the hillslope hydrology literature (e.g. Spence and Woo, 2003;Tromp-van Meerveld and McDonnell, 2006). The shape of the bedrock basin indicates a saddle at the south end of the meadow (Fig.…”
Section: Discussion: Synthesis Of Geophysical and Hydrological Resultsmentioning
confidence: 99%
“…Recent hydrological field studies in high-elevation watersheds have shown that during this high-flow melt period the contribution of subsurface flow to alpine streams can be as large as, if not larger than, that from surface flow (e.g. Sueker et al, 2000;Clow et al, 2003;Liu et al, 2004;Hood et al, 2006). In addition, although as much as 80% of total annual flow to alpine streams occurs during the Spring melting period from May to July (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Silica [Si] was selected as a tracer to characterize these end-members as it has been 11 used in previous studies to split groundwater contributions to bulk streamflow from dilute concentrations were calculated in the laboratory using the molybdosilicic method (ASTM 14 D859 -10). Basin specific, two end-member mixing models were used for hydrograph 15 separation approach to calculate meltwater and groundwater proportions for each reach using 16 simple mass-balance equations (Sueker et al, 2000). 17…”
Section: Ss = G S Dmentioning
confidence: 99%